2007
DOI: 10.2355/isijinternational.47.62
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbonisation Conditions on Mineral Matter in Coke

Abstract: The mineral phases present in coke contribute to coke degradation in the blast furnace. The mineral phases in coke are developed during coal carbonization process. Four Australian bituminous coals have been selected. Sub-samples from each coal were carbonized in three ovens of different capacity, and the carbonization parameters were also different. The mineral phases in cokes were identified in the low temperature ashed samples using X-ray diffraction technique. Amorphous alumino-silicate was the dominant pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…The EDX semi-quantitative analysis of this coke converted to oxides in mineral matter (Table 3) shows a clear prevalence of Al 2 O 3 that had along with SiO 2 a major presence, in different ratios, also in other found coke breeze residues. Such presence of components is in agreement with the general nature of coke the mineral components of which are of the strongly acidic nature [11]. The ratio of CaO in the coke mineral matter varies but normally it is very low.…”
Section: Sinters Prepared Using Charcoalsupporting
confidence: 67%
“…The EDX semi-quantitative analysis of this coke converted to oxides in mineral matter (Table 3) shows a clear prevalence of Al 2 O 3 that had along with SiO 2 a major presence, in different ratios, also in other found coke breeze residues. Such presence of components is in agreement with the general nature of coke the mineral components of which are of the strongly acidic nature [11]. The ratio of CaO in the coke mineral matter varies but normally it is very low.…”
Section: Sinters Prepared Using Charcoalsupporting
confidence: 67%
“…10-12 were designed to match the composition of mullite (No. [13][14][15]. Similarly, the alumina-silica ratios in combinations No.…”
Section: Mineralsmentioning
confidence: 95%
“…12) Further, when the analogue was produced using coke ash as the mineral component, it was found that the reactivity of coke analogue was similar to that of the cokes used to make the ash. 13,14) Quartz is one of the most commonly found minerals in cokes, 6,15,16) and has also been shown to reduce the reactivity of coke under CRI conditions. 6,7) Aluminosilicate minerals are also commonly found in cokes, 6,10,11,15,16) often having been present in the parent coals as clay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also been reported7–9 in which coke ash mineralogical composition is analysed by X‐ray diffraction (XRD), with a view to finding a relationship between the ashes and coke reactivity. No studies are available in the literature, however, in which a complete chemical characterisation is performed of petroleum cokes by a simple, rapid, and reliable method that could be readily used as a control method.…”
Section: Introductionmentioning
confidence: 99%